Who supports the populist radical right? The determinants of vote for Chega : a case-study of populist radical right voters in Portugal : 2019-2022 - Mantas, Catarina Antunes (2022)
This dissertation evaluates who votes on Chega in three domains, a) socioeconomic profile, b) voter transference and c) electoral geography for three landmarks: 2019 and 2022 legislative elections, and the 2021presidential election. Through a descriptive analysis combining Centro de Estudos e Sondagens de Opinião (Centre for Studies and Opinion Polls, CESOP) exit polls and election data of Secretaria Geral do Ministério da Administração Interna (Secretary General of the Ministry of Internal Affairs, SGMAI, SGMAI), this investigation finds that Chega’s electorate has a greater proportion of male voters aged 25-54 who completed high school than the electorate as a whole. Also, those voting on Chega previously voted on Partido Social Democrata (Social Democratic Party, PSD) to a greater extent or, to a lesser extent, did not vote at all. Support for Chega is disproportionately low in Northern regions. The main contribution of this study is the analysis of a large sample of the electorate of Chega. Comparisons between the findings on the profile of Chega’s voters and that of populist radical right voters in France, Italy, and Spain corroborate theories that there is no single populist radical right voter. Future studies should evaluate the attitudinal profile of Chega’s voters and introduce supply-side variables.